VALUE ADDED ANALYSIS OF WATER HYACINTH BAGS AS REGIONAL FEATURED PRODUCT - Khoirul Hidayat; M Yaskun; M. Adhi Prasnowo (Teknika: Engineering and Sains Journal, 2018)
Research has a purpose and direction to maximize the value of water hyacinth. The condition of water hyacinth which has a high growth speed so that this plant is considered as a weed that can damage the aquatic environment. Water hyacinth is easily spread through water channels to other water locations, so the growth of water hyacinth can develop rapidly. So far, water hyacinth has become a problem for the community, because the presence of water hyacinth is not smooth, reservoirs and swamps are dirty. One of the processed products of water hyacinth is the bag. Thereforethe implementation of research leads to an analysis of the added value (added value) of water hyacinth into the water hyacinth bag. This study uses the Hayami method and descriptive analysis. The use of descriptive analysis to obtain data about raw materials and the use of additional materials to produce water hyacinth bags, then the results go to the value-added analysis with the Hayami method. The results of this study indicate that the added value (added value) obtained from the processing of water hyacinth into the water hyacinth bag in Ghandis Craft is Rp. 10,000/kg or IDR. 50,000/product, with a ratio of value added to the output value of 50% which has a value of greather than or equal to 40% so that it has a high value-added category with a workforce income of 53,333%, the contribution of other inputs 33,333%, and the profit of entrepreneurs is 13,333%. Whereas in R & D Handicraft is IDR. 8,000/kg or IDR. 40,000/product, with a ratio of value added to the output value of 44,444% which has a value of greather than or equal to 40% so that it has a high value-added category with a workforce income of 53,846%, the contribution of other inputs 38,462%, and the entrepreneur's profit of 7,692%. Therefore, the manufacture of water hyacinth bag products provides high added value because of more than 40%.